Conspicuous By Its Absence: Ethics and Managerial Economics - Arce M., Daniel G. (Journal of business ethics, 2004)
This paper gives prescriptions for introducing ethical concerns into the economic theory of the firm. Topics include social responsibility, corporate governance, profit maximization, competition barriers, collusion, the market system, and welfare economics. The need for such prescriptions is based on a content analysis of 21 managerial economics texts for their coverage of ethics. My analysis finds that substantive discussions of ethics are conspicuous by their absence. As ethical breaches can involve significant monetary damages to a firm – particularly through adverse market reactions – moral-reasoning abilities can complement analytical skills. Consequently, my analysis demonstrates how ethics figure into the opportunity costs of managerial decision making, which is central to the economic definition of profit.